Pengaruh Sosialisasi Psikologi Keluarga Terhadap Pemahaman Ibu dalam Pengasuhan Positif pada Anak - Julianto, Rahmad (Pusat Studi Wanita UIN Ar-Raniry, 2025)
Parenting patterns implemented by parents play a significant role in shaping children's behavior, self-regulation skills, and readiness to face environmental demands. However, in practice, many parents still apply parenting patterns based on traditional customs and values ​​without an adequate understanding of developmental psychology-based parenting principles. This condition was also found in the community of Gampong Rumpet, Krueng Barona Jaya District, Aceh Besar Regency, which was the research area. This study aims to improve mothers' understanding of positive parenting through family psychology socialization. The descriptive quantitative approach method with a one-group pretest-posttest design. The respondents were 27 mothers who participated in the socialization. Data analysis used a paired samples t-test. The results showed a significant increase in mothers' understanding with an average pretest score of 4.37 to 6.48 in the posttest average score, and the results of statistical tests showed a significant difference between the pretest and posttest scores (t = 9.786; p = 0.000). These findings suggest that family psychology socialization is effective in increasing children's understanding of positive parenting. This is expected to become a family empowerment strategy to support the implementation of more balanced, adaptive parenting styles that meet the developmental needs of today's children.